Management of foliar and soilborne pathogens of cowpea (Vigna unguiculata L. walp) with two garlic varities (Allium Sativum A.Linn) (2014)
White and pink garlic extracts were tested for their antifungal potentials on mycelial radial growth, spores and sclerotial production of Macrophomina phaseolina (Tassi) Goid, Colletotrichum destructivum O gara and Colletotrichum capsici (Syd) Butter and Bisby pathogens of cowpea in vitro. Water or ethanol extracts of common pink and common white garlic varieties were tested at a concentration of 250 ppm while sterile distilled water served as control. In vivo study was based on white garlic extracted alone at 0.50 and 100% concentrations on M.phaseolina and C.capsici. Data were subjected to ANOVA and means was separated at P=0.05. Water extracted white garlic gave over 90% inhibitions of mycelial growth of M. Phaseolina and gave higher inhibitions than water or ethanolic pink garlic extracts on all the three pathogens. It is not significantly lower P=0.05 than conventional fungicide benomyl at 0.05 gai/kg. However, in vivo result was phytotoxic to cowpea seeds at 100% concentration and pathogrn control at 50% garlic extract. In contrast, cowpea variety IT84S-2246-4 seed germination was 77% when treated with M.phaseolina and 100% with C.capsici but reduced pathogen control at 50% garlic extract